Islamic Religious Education in the Era of Environmental Crisis: Interfaith, Interdisciplinary, and Interplanetary Perspectives - Oliver B. Wren; Lilis Nurteti; Muhamad Adnan bin Daud; Selamet; Husni (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
This study explores how Islamic Religious Education (Pendidikan Agama Islam/PAI) teachers perceive, integrate, and respond to the environmental crisis in their teaching practices, and their openness to interfaith, interdisciplinary, and “interplanetary” approaches as an expansion of ecological consciousness. This research employed a qualitative design, utilizing in-depth interviews with eight PAI teachers. Data was analyzed using thematic coding to identify key patterns and themes. The findings indicate that most teachers possess a good awareness of the environmental crisis and ethically and theologically link it to Islamic teachings. Nevertheless, the implementation of ecopedagogy in PAI classes remains largely incidental due to curriculum limitations and insufficient support. Interestingly, teachers demonstrated considerable openness to interfaith and interdisciplinary approaches for enriching the PAI curriculum, viewing them as means to enhance PAI's relevance. While the “interplanetary” idea remains speculative, glimmers of cosmic awareness are present in their narratives, potentially opening new theological insights. The implications suggest the need for explicit integration of ecological ethics into PAI curriculum and comprehensive teacher training modules, alongside the potential development of PAI based on spiritual-cosmological ecopedagogy.